2018
DOI: 10.12669/pjms.345.15772
|View full text |Cite
|
Sign up to set email alerts
|

Gum chewing and bowel function after Caesarean section under spinal anesthesia

Abstract: Objective:To determine the effect of gum chewing on bowel function postoperatively in women after cesarean delivery under spinal anesthesia.Methods:This semi-experimental study was conducted at Near East University Hospital Obstetrics and Gynecology Clinic in Turkish Republic of Northern Cyprus with 45 women in both the +experimental and control groups, between October 2016 and June 2017. The women in the experimental group chewed gum two hours after surgery until gut sounds were heard and nutrition was given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
2
4
1
2
Order By: Relevance
“…Our study showed that early mobilization after C-section conducted by a multidisciplinary health care team could singly shorten the time until the patient’s first ambulation, shorten the length of hospital stay and reduce complications after C-section. This result is consistent with those of many previous studies [ 18 , 19 ], and early mobilization after C-section can improve patient recovery. In the study, all of the clinical practices included in the intervention were successfully implemented except abdominal drainage tube removal within 24 h and activity recording by patients, and the onset time of off-bed activities decreased from 31.89 ± 9.50 h to 20.01 ± 4.65 h.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that early mobilization after C-section conducted by a multidisciplinary health care team could singly shorten the time until the patient’s first ambulation, shorten the length of hospital stay and reduce complications after C-section. This result is consistent with those of many previous studies [ 18 , 19 ], and early mobilization after C-section can improve patient recovery. In the study, all of the clinical practices included in the intervention were successfully implemented except abdominal drainage tube removal within 24 h and activity recording by patients, and the onset time of off-bed activities decreased from 31.89 ± 9.50 h to 20.01 ± 4.65 h.…”
Section: Discussionsupporting
confidence: 93%
“…Preoperative education and preoperative behavioural interventions have a direct impact on patients’ postoperative rehabilitation and were well documented in this study. According to previous study results, postoperative patients may suffer postoperative problems such as incision pain [ 19 ], intestinal distension [ 18 ], and incision site or urinary tract infections [ 19 , 20 ], and they would refuse mobilization. Therefore, preoperative education of patients is an important part of postoperative care in C-sections [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 .The study conducted by Akalper O et al,9 also shows similar results to our study, mean time to hear 1 st intestinal sounds after surgery in cases group is 12.6±7.7 hours and 16.3±5.2 hours in Control group with statistically significant difference between the groups.…”
supporting
confidence: 90%
“…As an alternative to sham feeding, chewing gum had been proved to be an effective measure to ameliorate gastrointestinal function and decrease complications such as nausea, vomiting and ileus after gynecological surgery 21 . Another clinical study also indicated that chewing gum in the postoperative could shorten the duration of the intestinal movement, the time of first flatus and defecation time of patients who had undergone cesarean operation 22 . In our study, the data revealed that the first flatus time of the XBP group was similar to that of chewing gum group.…”
Section: Discussionmentioning
confidence: 97%